Cardiopulmonary exercise testing is a better outcome predictor than exercise echocardiography in asymptomatic aortic stenosis. (15th January 2017) - Domanski, Olivia; Richardson, Marjorie; Coisne, Augustin; Polge, Anne-Sophie; Mouton, Stephanie; Godart, François; Edmé, Jean Louis; Matran, Regis; Lancellotti, Patrizio; Montaigne, David
Abstract: Background: Objective assessment of maximal aerobic capacity using peak oxygen consumption (peak VO2) can be helpful in the management of patients with asymptomatic aortic stenosis (AS). The relationship between peak VO2 and AS severity criteria derived from rest and supine exercise echocardiography (SEE) has never been explored. Objectives: We aimed to determine whether low peak VO2 (< 85% of predicted value) is associated with severity parameters in SEE, and poor clinical outcome. Methods: Fifty one asymptomatic patients (mean age of 54 ± 21 years) with moderate to severe aortic stenosis (Vmax > 3 m/s) and left ventricle ejection fraction > 50% prospectively underwent resting and SEE and cardiopulmonary exercise testing (CPX). Results: Peak VO2 was lower than expected (21.9 ± 7.4 mL/kg/min), i.e. < 85% of predicted value in 57% patients, secondary to cardiac limitation in most of them (69%). In multiple regression analysis, age, BMI and female gender were the only independent determinants of peak VO2. Interestingly no parameter derived from SEE was associated with peak VO2. After 21 ± 7 month follow-up, no patient died, 20 underwent cardiac surgery. Peak VO2 < 85% of predicted value was associated with lower event free survival compared to normal peak VO2 (57% ± 11% vs 93 ± 6%, p = 0.036) whereas no exercise echocardiographic parameter could predict such events. Peak VO2 ≥ 85% had a negative predictive value of 97%. Conclusion: CPX detects a high proportion of false asymptomatic AS patients with poorer outcome that cannot be predicted by SEE markers of AS severity. Assessment of aerobic capacity should be part of current approach within a "watchful waiting" strategy.